MadR1, a Mycobacterium tuberculosis cell cycle stress response protein that is a member of a widely conserved protein class of prokaryotic, eukaryotic and archeal origin. Issue 3 (May 2015) - Crew, Rebecca; Ramirez, Melissa V.; England, Kathleen; Slayden, Richard A.
Summary Stress-induced molecular programs designed to stall division progression are nearly ubiquitous in bacteria, with one well-known example being the participation of the SulA septum inhibiting protein in the SOS DNA damage repair response. Mycobacteria similarly demonstrate stress-altered growth kinetics, however no such regulators have been found in these organisms. We therefore set out to identify SulA-like regulatory proteins in Mycobacterium tuberculosis. A bioinformatics modeling-based approach led to the identification of rv2216 as encoding for a protein with weak similarity to SulA, further analysis distinguished this protein as belonging to a group of uncharacterized growth promoting proteins. We have named the mycobacterial protein encoded by rv2216 morphology altering division regulator protein 1, MadR1. Overexpression of madR1 modulated cell length while maintaining growth kinetics similar to wild-type, and increased the proportion of bent or V-form cells in the population. The presence of MadR1-GFP at regions of cellular elongation (poles) and morphological differentiation (V-form) suggests MadR1 involvement in phenotypic heterogeneity and longitudinal cellular growth. Global transcriptional analysis indicated that MadR1 functionality is linked to lipid editing programs required for growth and persistence. This is the first report to differentiate the larger class of these conserved proteins from SulA proteins and characterizes MadR1 effects on the mycobacterial cell.